2022
DOI: 10.1093/stcltm/szac081
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stromal Cells for Chronic Wounds: Scientific Evidence and Roadmap Toward Clinical Practice

Abstract: Chronic wounds, ie, non-healing ulcers, have a prevalence of ~1% in the general population. Chronic wounds strongly affect the quality of life and generate considerable medical costs. A fraction of chronic wounds will heal within months of appropriate treatment; however, a significant fraction of patients will develop therapy-refractory chronic wounds, leading to chronic pain, infection, and amputation. Given the paucity of therapeutic options for refractory wounds, cell therapy and in particular the use of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…Thus, the gelatin-based delivery studied here represents an attractive, non-invasive route, which maximizes the local efficacy of ASC therapy for chronic wound care without toxicity/tumorigenicity. The risk of side effects of ASC/gelatin therapy are considered to be limited because (i) clinical-grade gelatin is widely used in surgery worldwide (as hemostatic sponges), and (ii) ASC have been extensively studied and administrated through many delivery routes, showing an excellent tolerance in humans [ 5 ]. First-in-human studies are planned soon to clinically validate the use of the ASC-patch solution as a simple and effective treatment improving patient compliance and physician acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the gelatin-based delivery studied here represents an attractive, non-invasive route, which maximizes the local efficacy of ASC therapy for chronic wound care without toxicity/tumorigenicity. The risk of side effects of ASC/gelatin therapy are considered to be limited because (i) clinical-grade gelatin is widely used in surgery worldwide (as hemostatic sponges), and (ii) ASC have been extensively studied and administrated through many delivery routes, showing an excellent tolerance in humans [ 5 ]. First-in-human studies are planned soon to clinically validate the use of the ASC-patch solution as a simple and effective treatment improving patient compliance and physician acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the presence of guidelines, severe ulcers are not efficiently managed with current therapies. In this respect, cell therapy based on adipose-derived stromal cells (ASC) has emerged as particularly promising [ 5 , 6 ]. Several in vitro and pre-clinical animal studies have demonstrated that ASC exert beneficial effects on wounds [ 5 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain reduction in those patients is related to the ADSCs exhibiting immunosuppressive characteristics and minimal immunogenicity, making them excellent for transplantation to painful and injured sites; also, their ability to release trophic factors improves the therapeutic and corrective outcome 33,34 …”
Section: Discussionmentioning
confidence: 99%